The Influence of Semboro Citrus Brand on Market Competition and Income Generation of Citrus Farmers in Umbulsari Sub District - Mh Taufiqur Rohman, Mh. Taufiqur Rohman; Syarofi, Muhammad; Abdul Jawad, Islam (Jurnal Rekoginisi Ekonomi Islam, 2024)
The purpose of this study was to determine whether there is an influence between semboro citrus brands on competition and increased income of citrus farmers in Umbulsari District. This research is a quantitative study using the survey method, sampling with probability sampling techniques using simple random sampling method, 96 citrus farmers in Umbulsari District were selected as respondents. Data analysis techniques using Structural Equation Modeling (SEM) method with SmartPLS version 3.0 analysis software. The results showed that semboro citrus brand has a significant effect on market competition, this proves that H1 (accepted) and semboro citrus brand has a significant effect on the income of citrus farmers in Umbulsari District, this proves that H2 (accepted).